Perovskite catalysts for hydrogen production from hydrogen sulfide - Guldal, Nafi O.; Figen, Halit Eren; Baykara, Sema Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Hydrogen production via catalytic thermal decomposition of hydrogen sulfide (H2S) was studied experimentally by synthesizing, characterizing and testing perovskite type catalysts; A(x)A'(1-x)ByB'O-(1-y)(3). In the formulation, A and A' represented La and Sr respectively, B was chosen as Cr, and B' was either Co or Mo or V. The subscript x of the perovskite structure was 0.9 and y values were 1, 0.75, 0.5 and 0.25. Catalytic thermal splitting of H2S was conducted in a continuous flow quartz reactor at atmospheric pressure and at temperatures ranging from 600 degrees C to 1000 degrees C using 150 ml/min H2S (1% vol.) total volumetric flow rate. The optimum Cr:Co ratio was found to be 0.33 at 950 degrees C where maximum equilibrium conversion of 36.3% was achieved with La0.9Sr0.1Cr0.25Co0.75O3. The perovskite involving Mo had a similar catalytic performance of 35.2%, at 950 degrees C. Direct thermal decomposition of hydrogen sulfide showed only 5.5% and 22.4% conversions at 900 degrees C and 950 degrees C respectively, which were far below the corresponding conversion values achieved with catalysts. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Thermal decomposition; Hydrogen sulfide; Hydrogen production; Catalyst; Perovskite; THERMAL-DECOMPOSITION; THERMOCHEMICAL DECOMPOSITION; H2S; COMBUSTION; STABILITY; VANADIUM; METHANE; SULFUR; LACRO3; OXIDE; Chemistry; Electrochemistry; Energy & Fuels